2018
DOI: 10.1002/ajim.22928
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of autocoding programs for converting job descriptors into standard occupational classification (SOC) codes

Abstract: Background Existing datasets often lack job exposure data. Standard Occupational Classification (SOC) codes can link work exposure data to health outcomes via a Job Exposure Matrix, but manually assigning SOC codes is laborious. We explored the utility of two SOC autocoding programs. Methods We entered industry and occupation descriptions from two existing cohorts into two publicly available SOC autocoding programs. SOC codes were also assigned manually by experienced coders. These SOC codes were then linked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 16 publications
3
8
0
Order By: Relevance
“…For analysis, we treated the manually coded occupation on the death certificate as if it were a gold standard, though we acknowledge that coding procedures may vary from state to state. In a prior comparison of manually coded versus auto‐coded job titles, SOC codes were assigned independently by two coders with differences resolved by consensus 7 . Our study observed similar agreement to this previous validation study, supporting the use of the death certificate code as a comparison standard.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…For analysis, we treated the manually coded occupation on the death certificate as if it were a gold standard, though we acknowledge that coding procedures may vary from state to state. In a prior comparison of manually coded versus auto‐coded job titles, SOC codes were assigned independently by two coders with differences resolved by consensus 7 . Our study observed similar agreement to this previous validation study, supporting the use of the death certificate code as a comparison standard.…”
Section: Discussionsupporting
confidence: 80%
“…Overall, we found good agreement for both the NIOCCS and SOCcer autocoding programs for assigning occupation codes that match manual coding. A previous study validating autocoding systems in two occupational cohort studies with self‐reported text‐based occupations found similar agreement with 64.0%–67.4% for major occupation codes for NIOCCS and 62.4%–72.3% for SOCcer 7 . For detailed occupation codes (6‐digit), we found a higher percent agreement than the former study and a lower percent agreement for major occupation (2‐digit) occupation codes.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Users of JEM must consider the source of exposure data – expert assessments, data collected from individual workers, or environmental sampling. The coding of occupations is time consuming and can introduce error ( 9 ), and more testing of and comparison with automated job coding systems is needed ( 10 ). JEM reflect an “average” level of exposure within a job at the expense of individual variation.…”
mentioning
confidence: 99%